Beam-based reconstruction of the shielded quench-heater fields for the LHC main dipoles. Issue 1 (1st January 2023) - Richtmann, L; Bortot, L; Ravaioli, E; Wiesner, C; Wollmann, D
Abstract: Small orbit oscillations of the circulating particle beams have been observed immediately following quenches in the LHC's superconducting main dipole magnets. Magnetic fields generated during the discharge into the quench heaters were identified as the cause. Since the resulting, shielded field inside the beam screen cannot be measured in-situ, the time evolution of the field has to be reconstructed from the measured beam excursions. In this paper, the field-reconstruction method using rotation in normalized phase space and the optimized fitting algorithm are described. The resulting rise times and magnetic field levels are presented for quench events that occurred during regular operation as well as for dedicated beam experiments. Finally, different approaches to model the shielding behavior of the beam screen are discussed.